2020
DOI: 10.1155/2020/3979630
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Fluid Balance and Pathophysiology of Myocardial Edema in Coronary Artery Bypass Grafting

Abstract: Myocardial edema is one of the most common complications of coronary artery bypass grafting (CABG) that is linearly related to many coronary artery diseases. Myocardial edema can cause several consequences including systolic dysfunction, diastolic dysfunction, arrhythmia, and cardiac tissue fibrosis that can increase mortality in CABG. Understanding myocardial fluid balance and tissue and systemic fluid regulation is crucial in order to ultimately link how coronary artery bypass grafting can cause myocardial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Accumulation of fluid in the intravascular and interstitial spaces in cardiac tissue results in cardiac load, leading to congestion triggered by cardiac edema [ 56 ]. Mishra (2018) [ 57 ] demonstrated that EAC triggers cardiac dysfunction traced by congestion scores.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of fluid in the intravascular and interstitial spaces in cardiac tissue results in cardiac load, leading to congestion triggered by cardiac edema [ 56 ]. Mishra (2018) [ 57 ] demonstrated that EAC triggers cardiac dysfunction traced by congestion scores.…”
Section: Discussionmentioning
confidence: 99%
“…In some early studies, the Bretschneider solution was considered the culprit for causing myocardial edema, especially in complex cardiac interventions with prolonged cardiac arrest and repeat administration [ 78 , 79 ]. The resulting myocardial edema could impair ventricular functioning due to wall stiffening, decreased diastolic compliance, interstitial tissue fibrosis, and could make the heart more susceptible to conduction disturbances or arrhythmias [ 80 ]. More recent studies advocate protection against myocardial edema with the use of HTK, mainly due to mannitol content [ 81 ].…”
Section: Bretschneidermentioning
confidence: 99%